2009
DOI: 10.1172/jci38374
|View full text |Cite
|
Sign up to set email alerts
|

Adoptive immunotherapy with liver allograft–derived lymphocytes induces anti-HCV activity after liver transplantation in humans and humanized mice

Abstract: After liver transplantation in HCV-infected patients, the virus load inevitably exceeds pre-transplantation levels. This phenomenon reflects suppression of the host-effector immune responses that control HCV replication by the immunosuppressive drugs used to prevent rejection of the transplanted liver. Here, we describe an adoptive immunotherapy approach, using lymphocytes extracted from liver allograft perfusate (termed herein liver allograft-derived lymphocytes), which includes an abundance of NK/NKT cells t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
76
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 57 publications
(79 citation statements)
references
References 42 publications
3
76
0
Order By: Relevance
“…In addition to their antitumor activity, NK cells might exert antiviral activity (4,44,45). Although the precise role of NK cells in this context requires further clarification (4,46), NK and NKT cells from liver allograft perfusates, infused after liver transplantation, reduced HCV RNA serum titers (47), suggesting that the application of expanded NK cells in this context is worthy of further study.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to their antitumor activity, NK cells might exert antiviral activity (4,44,45). Although the precise role of NK cells in this context requires further clarification (4,46), NK and NKT cells from liver allograft perfusates, infused after liver transplantation, reduced HCV RNA serum titers (47), suggesting that the application of expanded NK cells in this context is worthy of further study.…”
Section: Discussionmentioning
confidence: 99%
“…Activated liver allograftderived NK cells were isolated from the perfusate (IL-2 stimulated and anti-CD3 monoclonal antibody treated to deplete T cells), and injected intravenously into the transplant recipient. Early data from the pilot study reported lower HCV RNA titers at one month post-transplant, but the effect was transient [94] . Augmentation of the NK cell response, which plays a pivotal role in innate immunity, may be an alternative approach to preventing HCV recurrence and is an area of active research [95] .…”
Section: Anhepatic Initiated Therapy Thymoglobulin Inductionmentioning
confidence: 96%
“…The enhancement of the natural killer cellular response that plays a pivotal role in innate immunity may be a promising immunotherapeutic approach, also in the prevention of HCV recurrence post-LT [121] . Ohira et al [122] report an interesting immunotherapeutic approach for preventing post-transplant HCV recurrence, based on adoptive transfer of interleukin 2 (IL-2)/anti-CD3 monoclonal antibody (OKT3)-treated liver allograft-derived lymphocyte pools enriched in natural killer and natural killer T cells.…”
Section: Adoptive Immunotherapymentioning
confidence: 99%